Outcome of total laparoscopic hysterectomy in relation to the size of the uterus - Ajjammanavar, Virupakshi; P., Vinodini; S., Jayashree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Laparoscopic hysterectomy is a safe and feasible technique to manage benign uterine pathology as it offers minimal postoperative discomfort; with shorter hospital stay, rapid convalescence and early return to the activities of daily living. However, to date very few studies have been reported on safety and feasibility of total laparoscopic hysterectomy (TLH) in large sized uteri. The present study was planned to evaluate the intra-operative and post-operative parameters in relation to size of the uterus during TLH. Methods: This study was a comparative study. Fifty women with uterine size less than 12 weeks (Group 1) and fifty women with uterine size more than or equal to 12 weeks (Group 2) for whom TLH was planned for benign indications were included in the study. Intra-operative and post-operative parameters like blood loss, duration of surgery, post-operative pain and complications were compared between the two groups. Comparison was done using independent sample t test. A probability (‘p’ value) of less than or equal to 0.05 at 95% confidence interval was considered as statistically significant. Results: The mean age of the patients in both the groups was matched (44.82 years vs. 43.96 years). The mean operative time (48.80±14.12 minutes vs. 77.3±35.11 minutes; p <0.001) and blood loss (40.10±18.25ml vs. 70.6±65.46 ml; p=0.002) were significantly high in Group 2 compared to Group 1. The mean pain scores were similar in both the groups at 6 hours, 24 hours and at the time of discharge. No significant complications were noted in both the groups. Conclusions: TLH is safe, feasible and acceptable for large size uterus (>12 weeks). However, it is associated with longer operative time, and greater amount of blood loss.